Harmonization of State, Custom, and Islamic Law in Aceh: Perspective of Legal Pluralism - Djawas, Mursyid; Nurdin, Abidin; Zainuddin, Muslim; Idham, Idham; Idami, Zahratul (Hasanuddin Law Review, 2024)
Indonesia recognizes several legal systems i.e., state law, customary law, Islamic law, and international law. Islamic sharia in Aceh is part of legal pluralism in Indonesia. This study aims to discuss the application of Islamic sharia from the perspective of legal pluralism. This normative legal study employed a legal pluralism theory analysis. Legal pluralism is a theory that views law not only as positive or written law made by the state but also as a recognition of the legal reality that exists in a pluralistic society. The study collected data by means of a literature review. Findings revealed that Islamic sharia in Aceh as part of the recognition of the concept of legal pluralism has been implemented well in the context of state law, custom, and Islamic law. The state has provided juridical legitimacy through laws in the context of legal substance and judicial institutions or sharia courts. Likewise, revitalization has also occurred in traditional institutions in terms of customary law and customary justice. The argument emphasized in this study is that Islamic sharia in the context of legal pluralism has succeeded in manifesting legal harmonization between the state, custom, and Islamic law